Frequent intentional weight loss is associated with higher ghrelin and lower glucose and androgen levels in postmenopausal women - Hooper, Laura E.; Foster-Schubert, Karen E.; Weigle, David S.; Sorensen, Bess; Ulrich, Cornelia; McTiernan, Anne (Nutrition research, 2010)
Population-based studies suggest that repetitive cycling of weight loss and regain may be associated with future weight gain. Therefore, to better define the relationship between weight cycling, energy homeostasis, and future weight gain, we examined associations between frequent intentional weight loss and hormonal profiles in postmenopausal women. This cross-sectional study evaluated the relationship between a history of frequent weight loss and biomarkers, including serum glucose, insulin, leptin, and ghrelin, as well as sex steroid hormones. We hypothesized that frequent intentional weight loss would be associated with changes in normal appetite and body weight regulatory hormones, favoring increased appetite and weight gain. One hundred fifty-nine healthy, weight stable, sedentary, overweight, postmenopausal women who had been recruited for an exercise intervention participated in this study. History of intentional weight loss (frequency and magnitude) was assessed by questionnaire. Hormonal assays were performed by radioimmunoassay (insulin, leptin, ghrelin, estrogens, androgens, and dehydroepiandrosterone), chemiluminescence immunoassay (insulin-like growth factor-1), and immunometric assay (sex hormone binding globulin). Analysis of variance and regression analyses were used to investigate the relationship between weight loss history and metabolic hormones. A higher degree of weight cycling, characterized by the frequency of intentionally losing more than 10 lb, was associated with an appetite-stimulating hormonal profile, including higher concentrations of ghrelin (P trend = .04), lower glucose (P trend = .047), and to some extent, lower insulin (P trend = .08). Frequent weight loss was also associated with lower androgen concentrations, including androstenedione (P trend = .02), testosterone (P trend = .04), and free testosterone (P trend = .01). No independent associations between the concentrations of leptin or estrogens and weight cycling were observed. This study suggests that frequent intentional weight loss may affect hormones involved in energy regulation.